Community Health Workers Promoting Physical Activity: Targeting Multiple Levels of the Social Ecological Model - Haughton, Jessica (J Ambul Care Manage, 2015)
The effectiveness of community health workers (CHWs) as health educators and health promoters among Latino populations is widely recognized. The Affordable Care Act created important opportunities to increase the role of CHWs in preventive health. This article describes the implementation of CHW-led, culturally specific, faith-based program to increase physical activity among churchgoing Latinas. This study augments previous research by describing the recruitment, selection, training, and evaluation of CHWs for a physical activity intervention targeting multiple levels of the Social Ecological Model.